Semantic and syntactic language differences associated with the FMR1 premutation genotype - Friedman, Laura; Matchin, William; Berry-Kravis, Elizabeth; Klusek, Jessica (Journal of neurolinguistics, 2026)
The FMR1 premutation genotype occurs in approximately 1 in 150 women and 1 in 470 men. New evidence suggests that the FMR1 premutation may be associated with language differences, although the breadth of language challenges, specific domains affected, and potential interface with executive aspects of the phenotype are not fully understood given the lack of targeted studies. The present study compared the language skills of 109 women with the FMR1 premutation to 109 age-, education-, and nonverbal IQ-matched control women, using a series of standardized language repetition tasks to index language abilities within a measurement context that reduces the influence of higher-order executive deficits. Results indicated that, relative to controls, women with the FMR1 premutation performed significantly worse on tasks assessing semantic and syntactic, but not phonological, skills. Group differences could not be accounted for by attention or working memory difficulties. This study documents semantic and syntactic language differences associated with the FMR1 premutation genotype. Findings may have implications for identifying gene-brain-behavior mechanistic pathways, with more research needed to characterize the clinical impact of language differences associated with this genotype. FMR1 may play a role in mediating some aspects of language in the population. •We compared language skills in a large sample of FMR1 premutation women to controls.•Women with the FMR1 premutation had poorer semantic and syntactic language skills.•Phonological language skills were not worse in women with the FMR1 premutation.•Language weaknesses could not be accounted for by executive deficits.•Findings suggest a potential role of FMR1 in mediating some aspects of language.